Students’ Perspectives on Explicit Teaching in Reading Comprehension in an Online Classroom - Anit Pranita Devi; Suroto Suroto (Siliwangi University, 2021)
This study examines students’ perspectives of the implementation of explicit teaching of reading comprehension strategies in an online academic reading classroom context at a university in Sumedang, Indonesia. The study employs qualitative research design embracing the characteristics of a case study. The data are obtained from an in-depth interview of students involved in the online This study examines students’ perspectives of the implementation of explicit teaching of reading comprehension strategies in an online academic reading classroom context at a university in Sumedang, Indonesia. The study employs qualitative research design embracing the characteristics of a case study. The data are obtained from an in-depth interview of students involved in the online academic reading classroom who have been taught using explicit reading strategies instruction for one semester. The objectives of the study are to explore students' perspectives of the role of the reading instructor, how the explicit instruction assists them in improving their academic reading, and the obstacles they find during the instruction. The data are analyzed descriptively by conducting data reduction and categorizing the data based on the three aspects formerly mentioned. The interview result points out a positive view about the implementation of explicit teaching of reading strategies and its effects on the students’ academic reading improvement. The students also emphasize an essential role of the reading instructor in guiding the students to master academic reading strategies in the online classroom environment. The major obstacles encountered by the students are common technical problems like connection, audio and video as well as the problems with their fluctuating motivation in doing the online learning. However, all these problems are not related to their positive view about the application of the explicit teaching of reading strategies in the classroom. Keywords: explicit teaching, reading comprehension strategies, students’ perspectives